EFEK KOMUNIKASI, SUPPORT KELUARGA DAN KECERDASAN EMOSI TERHADAP PRESTASI BELAJAR SISWA DI SDIT MA’ARIF MAKASSAR - Halik, Syahrul; Fajriah, Yana; Idris, Ma'ruf (AkMen JURNAL ILMIAH, 2024)
The purpose of this study is to analyze the influence of Communication, Family Support and Emotional Intelligence on Student Learning Achievement at SDIT Ma'arif Makassar. The research approach used in this study is quantitative research because this study aims to prove the hypothesis, using research instruments on teachers at SDIT Ma'arif Makassar. In this study, the research population of SDIT Ma'arif Makassar teachers was 38 teachers. The sampling method is a saturated sample technique. So the sample in this study is 38 samples. In this study, the author used multiple linear regression analysis.